Problematika Pembelajaran Daring Di SDN Jelapat Baru Kabupaten Barito Kuala - M. Ihsan Ramadhani (Tut Wuri Handayani : Jurnal Keguruan dan Ilmu Pendidikan, 2022)
This study aims to (a) find out the problems of online learning during the COVID-19 pandemic at SDN Jelapat Baru, Barito Kuala Regency, and (b) find out the impact of online learning on student learning outcomes at SDN Jelapat Baru, Barito Kuala Regency. The method used is a qualitative research method using data collection techniques, namely interviews and documentation. Interview technique by collecting information from school principals, high grade homeroom teachers, high grade students and parents of high grade guardians. The data analysis technique uses several stages, namely: organizing data, grouping based on categories, themes and patterns of answers, testing assumptions or existing problems with data, looking for alternative explanations for data and writing research results. Based on the results of the study, it was found that several problems of online learning during the COVID-19 pandemic were found, namely the lack of availability of internet access, there were still students who did not have the tools used as the main media in online learning such as gadgets, some students were still constrained by not having access to the internet. the tools used for online learning media are gadgets, students' lack of sense of responsibility towards assignments, students find it difficult to understand lessons, lack of quotas in learning. The impact of online learning on the learning outcomes of high-grade students at SDN Jelapat Baru, Barito Kuala Regency, during online learning, did not experience a drastic increase or decrease in grades when online learning was implemented.